2017
DOI: 10.1016/j.astropartphys.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

EAS age determination from the study of the lateral distribution of charged particles near the shower axis with the ARGO-YBJ experiment

Abstract: Neutrino physics, Low-background physics, Underground physics, Neutrinoless double-beta decay, Neutrino mass, Ultra-high energy cosmic rays Highlights Highlights are optional yet highly encouraged for this journal, as they increase the discoverability of your article via search engines. They consist of a short collection of bullet points that capture the novel results of your research as well as new methods that were used during the study (if any). Please have a look at the examples here: example Highlights. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…As a consequence, the relations between various shower characteristics represented using the cascade age parameter demonstrate to one degree or another the invariance with respect to the properties of a primary particle. Different aspects of the universality (phenomenology, possible generalisations, deeper understanding of the origin and limitations, sensitivity to the hadronic interaction model, applicability under conditions of real experiments) are subjected to remarkable interest [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Air Shower Universality and Scaling Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the relations between various shower characteristics represented using the cascade age parameter demonstrate to one degree or another the invariance with respect to the properties of a primary particle. Different aspects of the universality (phenomenology, possible generalisations, deeper understanding of the origin and limitations, sensitivity to the hadronic interaction model, applicability under conditions of real experiments) are subjected to remarkable interest [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Air Shower Universality and Scaling Formalismmentioning
confidence: 99%
“…This led to various modifications of the NKG form, such as changing the values of exponents, introducing different constant or variable scale factors, lateral (s ⊥ ) or local (s(r)) age parameters and also generalizations of the function by using a third power-law term. A comprehensive review is beyond the scope of this paper (some discussions can be found in [33,34,36,38,44]).…”
Section: Air Shower Universality and Scaling Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…With the full coverage array operated in the ARGO-YBJ experiment at the 4300 m asl, very close to the shower maximum, for the first time the shower core region has been studied with unprecedented details [18]. In addition, events are selected on an event-by-event basis exploiting the lateral distribution of secondary particles and not the muonic size, with results nearly independent from the hadronic interaction models.…”
Section: Open Problems In Cosmic Ray Physicsmentioning
confidence: 99%
“…The Nishimura-Kamata-Greisen (NKG) function [1,2] gives a good theoretical approach for the lateral distribution of electromagnetic particles, from which the dependency of the lateral growth of cascade on the energy, intensity and type of the primary cosmic rays can be clearly shown. Several ground-based observation experiments, such as ARGO-YBJ [3], KASKADE [4], NBU [5] and Utah neutrino detector [6], have reported the lateral distribution of secondary particles associated to the energy of primary cosmic rays. A few simulations have been done to study the lateral distribution.…”
Section: Introductionmentioning
confidence: 99%